Upaya Meningkatkan Soft Skill Santriwatiwati Melalui Pelatihan Pidato Bahasa Inggris - Eva Sulistiana (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Abstract: As a young generation who will face the era of globalization, in addition to the provision of religious knowledge from Islamic boarding schools, soft skills in English will be an added value for the female students. Based on the analysis of the problems faced by the community service team partners, they provided solutions in the form of English speech training for female students. This speech training involved 16 female students. In this training, mentoring was carried out by 3 non-native speaker tutors who provided corrections and feedback starting from the process of preparing speech texts to practicing speeches. The implementation method used in this training is 1) Accompanying the female students in preparing the speech text. 2) Practice pronunciation, expression and gesture in giving speeches. 3) Provide feedback for errors during practice. 4) Hold a speech competition for female students. The result of this training is that the female students appear confident when participating in the speech competition.